Case study: polyspecific immunoglobulin Y (IGY) therapy in a pelvilingual carcinoma diagnosed patient infected with Staphylococcus aureus methicillin-resistant - Teodora Supeanu; Alef Ibram; Camelia Apostol; Mariana Oporanu; Lucica Sima; Viorica Chiurciu; Constantin Chiurciu (Medicamentul Veterinar, 2019)
Infections caused by multidrug-resistant microbial agents often complicate the treatment of patients with severe primary conditions such as neoplasms, organ failure or chronic diseases. The methicillin-resistantStaphylococcus aureus (MRSA) is one of the main global-spread nosocomial bacteria for which significant efforts are currently being made to develop new therapeutic options. Avian immunoglobulin (IgY) is used in various fields of human and veterinary medicine, with proven action against a wide range of microbial infections (bacterial, fungal and viral). In this study, IgY was successfully administered to a patient with MRSA-overloaded neoplasm, being incorporated into therapeutic products for general administration and local applications.